Aspek Yuridis Kepemilikan Hak Atas Tanah Di Australia - Listyowati Sumanto (Jurnal Hukum PRIORIS, 2014)
Common law system in the commonwealth of Australia has affecting the conception of land law, particularly in land rights regulations, including on certain restrictions r prohibitions on land ownership. How does the type of land rights regulations and how is restrictions on land ownership by foreigners and foreign legal entities set forth in accordance with the Autralian Law? This study is used type of doctrinal legal research and descriptive. Qualitative anlysis required by doctrinal research. The types of land ownership has various periods of time, known as “estates”,  the y are consists of: (a) Fee simple, Fee and Fee Absolute or Estate or Freehold; (b) Fee Tail Esatate; (c) Life Estate; (d) Leasehold Foreigners and foreign legal entities intending to purchase real estate are subject to the provisions of the Foreign Acquisition and Takeovers Act 1975. An Applicatio n by a foreign investor must be made to the Foreign Investment Review Board (FIRB) who will the advise the Treasure to either approve or disallow the acquisition. The treasurer has provided an authorization to the Executive Member and other senior division staff of FIRB to make decision which are consistent with FIRB’s plicy. Proposals that involve issues of special sensitivity are decided by the Treasurer.Keywords: Land Rights, Autralian.